Bacterial keratitis in the critically ill. Issue 12 (1st December 1997) - Parkin, Ben; Turner, Andrew; Moore, Elizabeth; Cook, Stuart
Abstract : BACKGROUND: In the 4 year period (1988–91) there were nine cases of bacterial keratitis in five critically ill patients on an intensive care unit ('unit A'), all except one due to Pseudomonas aeruginosa . Many of these patients had serious ocular complications requiring surgery and all surviving patients were left with significant visual deficits. One further case of keratitis due to P aeruginosa occurred on unit A in April 1993. The problem of keratitis in ventilated patients is not unique to this unit as a further four cases in three patients from additional units in this area have been treated. METHODS: Predisposing factors in unit A were established through subsequent investigations. It was found, in particular, that all the ocular infections were preceded by colonisation of the respiratory tract with the pathogenic organism. Recommendations concerning eye care and tracheal suctioning were adopted by unit A in 1991. RESULTS: In the subsequent 4 years (1991–5), the frequency of isolation of pseudomonas from the respiratory tract per patient treated in unit A remained relatively high at 3.8% (153/4032). However, the conjunctival pseudomonas isolation rate has decreased significantly (p <0.001) from 0.8% (19/2430) to 0.05% (2/4032). CONCLUSIONS: Ventilated patients may be at risk from inoculation of pathogens into the eyes. The principal risk factor for bacterial keratitis in this series was corneal exposure secondary to conjunctival chemosis or lid damage. The adoption of simple preventative measures on unit A had a significant impact on the incidence of eye infections due to pseudomonas, despite the high proportion of patients whose respiratory tracts were colonised with the same organism. There is a need for additional research into the most effective method of eye care for ventilated patients in order to reduce the frequency of this avoidable condition.